Assessment of liver involvement in type 2 diabetes mellitus using fibroscan® and correlation with risk factors - ., Alagesan; Kumar, Sairam (International Journal of Advances in Medicine, 2019)
Background: Non‐alcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver injury. The most important predictor of mortality in NAFLD is the extent of liver fibrosis. Advanced liver fibrosis is associated with overall and liver related mortality. The upcoming non-invasive imaging modality for the evaluation of liver fibrosis is transient elastography (TE) (Fibro scan®). The aim of this study is to assess hepatopathy among diabetics using TE and to correlate the degree of hepatopathy with the associated risk factors. Methods: Type 2 diabetes mellitus patients were assessed for liver stiffness using TE. Liver stiffness was correlated with the associated risk factors. Authors recruited 100 patients from diabetic clinic in tertiary care teaching hospital. Results: About 55% of males and 39% of females had increased liver stiffness. 14% of males and 11% of females had severe fibrosis(F3-F4). Body mass index, waist circumference, fasting blood sugar levels, and liver enzymes, had significant positive correlation with liver stiffness whereas triglyceride levels, high-density lipoprotein levels, and duration of diabetes mellitus did not correlate with liver stiffness. Conclusions: Diabetic patients have high prevalence of NAFLD and advanced fibrosis. Those with obesity and dyslipidaemia are at particularly high risk. Type 2 diabetes mellitus patients with hepatopathy can be easily identified using TE scan eliminating the need for liver biopsy. The establishment of a national program for the recognition of NAFLD is essential to reduce the risk of liver disease progression.